2005
DOI: 10.1007/s00018-004-4412-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel racemization process of an asparaginyl residue in mouse lysozyme under physiological conditions

Abstract: We examined chemical reactions in mouse lysozyme after incubation under physiological conditions (pH 7 and 37 degrees C). After incubation for 8 weeks, racemization was observed specifically at Asn127 among the 19 Asp/Asn residues in mouse lysozyme. Furthermore, analysis of the primary structure showed that the racemized residue was not Asp, but Asn, which demonstrates that deamidation and isomerization did not occur. These results mean that this racemization occurs without forming a succinimide intermediate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Typically, the racemization occurs at Asp residues (138), although racemization at Asn 127 in murine lysozyme has been reported (139). Why this residue is more reactive is not yet known.…”
Section: Racemization and β-Eliminationmentioning
confidence: 98%
“…Typically, the racemization occurs at Asp residues (138), although racemization at Asn 127 in murine lysozyme has been reported (139). Why this residue is more reactive is not yet known.…”
Section: Racemization and β-Eliminationmentioning
confidence: 98%
“…Because Asp residues can be easily transformed into succinimidyl intermediates, the chiral inversion from L-Asp to D-Asp frequently occurs, therefore, D-Asp residues are often observed in disease/aged proteins [6]. However, some other D-amino acid residues, such as D-Ser and D-Asn, were also formed in a few protein samples [13][14][15]. These reports suggest that various D-amino acid residues are likely to occur without the formation of succinimidyl intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…[85] Other studies have cast doubt on the relevance of cyclic speciesf avouring ah omolysisvia ar adical. [126] Scheme22. Twoc ysteine residues drive racemisation in proline racemase.…”
Section: Racemisation (Or Epimerisation) Of Proteins and Amino Acidsmentioning
confidence: 99%
“…Recent results have suggested that anionic intermediates that have the possibility of aromatic character can enhance racemisation liability and it is noteworthy that the keto–enol tautomer of 55 would fall into this category . Other studies have cast doubt on the relevance of cyclic species favouring a homolysis via a radical …”
Section: Biological Racemisationmentioning
confidence: 99%